Molecular characterization and multi-environmental evaluation of field corn (Zea mays) inbreds for kernel traits - V, CHETHAN KUMAR; GADAG, R N; MUKRI, GANAPATI; BHAT, JAYANT S; SINGH, CHANDU; KUMARI, JYOTI; SINGH, RAJIV K; GUPTA, NAVIN C (The Indian Journal of Agricultural Sciences, 2021)
Kernel size and kernel weight are important yield attributing traits in maize (Zea mays L.). Though yield hascomplex inheritance, understanding and improvement of yield per se becomes relatively easy, when maize breedingis targeted for genetic enhancement of yield component traits. In the present investigation, a set of 45 tropical fieldcorn inbred lines were evaluated under three environments and at different location for kernel length, kernel thicknessand kernel weight traits. In a given location, environmental influence on the expression of these traits were negligibleas it was evident by exhibition of high heritability (broad sense) for the traits under study, however pooled effect ofenvironments showed some interactions. Based on the AMMI stability value, the inbred lines AI 04 followed by AI 37,AI 18, AI 25 and AI 35 were selected as highly stable genotypes for its yield per se. Inbred lines were characterizedusing gene-based markers linked to kernel traits. It was observed that molecular markers rightly classified the inbredlines into different groups based on their trait means. Furthermore, the makers, umc1890 and umc1120 were putativelylinked to kernel weight and kernel thickness respectively. These markers may be utilized for identification of suitabledonor and genetic improvement of kernel traits driven maize improvement program.